THEORETICAL FOUNDATIONS OF COMPETITIVE DEVELOPMENT MANAGEMENT DESIGN IN THE RESTAURANT BUSINESS - KOTOV, Oleksii (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The paper substantiates the theoretical foundations and practical recommendations for developing and implementing a management mechanism for the competitive development of restaurant enterprises. A framework comprising six interrelated theoretical propositions has been designed to elucidate the essence and specific characteristics of competitive development management in the restaurant industry. It is established that the competitive development of restaurant enterprises should be regarded as a dynamic process occurring within an open socio-economic system, which necessitates an ongoing adaptation to rapidly evolving consumer trends. The principles of management organization are substantiated, with particular emphasis on system integration and coherence, innovation orientation, customer-centric and experience-driven approaches, flexibility and adaptability, responsibility, and sustainable growth. A structured management mechanism for competitive development is proposed, encompassing the following components: a goal-setting block, a functional and administrative block, a resource allocation block, an organizational structure block, and a control and analytical block. The study presents an approach to competitive development through the selection of operational methods aligned with the characteristics of the chosen attractor of business activity. The necessity of continuously reassessing operational methods in response to the increasing digitalization of the economy is substantiated. Furthermore, the research highlights the dependence of competitive development on a restaurant's ability to uphold social responsibility and integrate into its institutional environment as a key node within a broader ecosystem. The developed conceptual framework visually aligns the principles of competitive development management with specific structural components of its implementation mechanism. The practical significance of these theoretical propositions lies in their potential to provide a foundation for continuously enhancing restaurant enterprises' competitive positioning by leveraging innovative management approaches, sustaining the uniqueness of service offerings, and ensuring long-term sustainable growth.
Keywords: competitive development; restaurant business; management mechanism; management principles; digitalization; social responsibility